Synthesis and redox behavior of a new polyanion compound, Li2Co2(MoO4)3, as 4 V class positive electrode material for lithium batteries - Begam, K. M.; Selladurai, S.; Michael, M. S.; Prabaharan, S. R. S. (2004)
A new material, Li2Co2(MoO4)(3), belonging to NASICON type polyanion family was synthesized by means of a low temperature soft-combustion method using glycine as a soft combustion fuel. The annealed product, Li2Co2(MoO4)(3), was found to exhibit a single phase structure as confirmed by XRD and crystallized in an orthorhombic structure (space group Prima) with lattice parameters a = 5.086(1) Angstrom, b = 10.484(2) Angstrom and c = 17.606(2) Angstrom. The electronic state of each element present in the new material was confirmed by X-ray photoelectron spectroscopic (XPS) analysis. The stoichiometry of the synthesized product was determined by the metal analysis using inductively coupled plasma (ICP-AES) technique. The microstructural analysis by means of SEM revealed cylindrical fiber-like grains. Electrochemistry of the new material was demonstrated by extraction/insertion process of Li+ in lithium batteries. Galvanostatic charge/discharge profiles revealed a reversible discharge capacity of similar to55 mAh/g over the potential window of 4.9 - 1.5 V.